Characterization, identification and purification of a high-affinity binding site for H4-(86-100) peptide in membrane preparations of rat alveolar macrophages - Bonhomme, Andreanne (University of Ottawa (Canada), 2003)
Rat alveolar macrophages express specific binding sites for C-terminal fragments of histone H4. The present study was aimed at identifying and characterizing the receptor for the C-terminal fragment 86 to 100 of histone H4, an antinociceptive peptide structurally similar to histogranin. The inhibitory effect of GTP analogs (GTP-gamma-S and Gpp(NH)p) and pertussis toxin on membrane preparations and the finding that H4-(86--100) potently (10--8 M) inhibited forskolin-stimulated cAMP levels in cultured alveolar macrophages suggest the involvement of a GiPCR. Gel electrophoresis of cross-linked bound radiolabelled ligand revealed two binding proteins, 30 kDa and 54 kDa, whose detection was increased by stimulation of macrophages with interferon gamma (IFNgamma). Affinity chromatography and SDS-PAGE gel electrophoresis revealed a major protein band identified as beta-actin trypsin digests. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.